Conditional effects of gain-loss-framed narratives among current smokers at different stages of change - Kim, Hye Kyung (2020)
This study examines how current smokers respond differently to gain-loss-framed antismoking narratives depending on their stages of change to quit smoking. An experiment (N = 461) was conducted with a 2 (narrative perspective: first person vs. third person) × 2 (framing: gain vs. loss) factorial design having smoker's stage of change (precontemplation vs. contemplation/preparation) as a moderator. We observed differential framing effects depending on smoker's current stages of change only when they were exposed to first-person narratives. For precontemplators, a loss-framed (vs. a gain-framed) first-person narrative induced greater quit intentions and stage progression. Conversely, among contemplators and preparers, a gain-framed (vs. a loss-framed) first-person narrative led to greater quit intentions and stage progression. These interactive patterns were partly mediated by self-referencing and perceived similarity. This study proposes an alternative mechanism to explain the conditional framing effect by stages of change and highlights the importance of tailoring messages to smoker's psychosocial characteristics and needs.